Maize/Soybean Relay Strip Intercropping Reduces the Occurrence of Fusarium Root Rot and Changes the Diversity of the Pathogenic Fusarium Species - Xiaoli Chang; Li Yan; Muhammd Naeem; Muhammad Ibrahim Khaskheli; Hao Zhang; Guoshu Gong; Min Zhang; Chun Song; Wenyu Yang; Taiguo Liu; Wanquan Chen (Pathogens, 2020)
Fusarium species are the most detrimental pathogens of soybean root rot worldwide, causing large loss in soybean production. Maize/soybean relay strip intercropping has significant advantages on the increase of crop yields and efficient use of agricultural resources, but its effects on the occurrence and pathogen population of soybean root rot are rarely known. In this study, root rot was investigated in the fields of the continuous maize/soybean strip relay intercropping and soybean monoculture. Fusarium species were isolated from diseased soybean roots and identified based on sequence analysis of translation elongation factor 1α (EF-1α) and RNA polymerase II second largest subunit (RPB2), and the diversity and pathogenicity of these species were also analyzed. Our results showed that intercropping significantly decreased soybean root rot over monoculture. A more diverse Fusarium population including Fusarium solani species complex (FSSC), F. incarnatum-equiseti species complex (FIESC), F. oxysporum, F. fujikuroi, F. proliferatum and F. verticillioides, F. graminearum and F. asiaticum was identified from intercropping while FSSC, FIESC, F. oxysporum, F. commune, F. asiaticum and F. meridionale were found from monoculture. All Fusarium species caused soybean root infection but exhibited distinct aggressiveness. The most aggressive F. oxysporum was more frequently isolated in monoculture than intercropping. FSSC and FIESC were the dominant species complex and differed in their aggressiveness. Additionally, F. fujikuroi, F. proliferatum and F. verticillioides were specifically identified from intercropping with weak or middle aggressiveness. Except for F. graminearum, F. meridionale and F. asiaticum were firstly reported to cause soybean root rot in China. This study indicates maize/soybean relay strip intercropping can reduce soybean root rot, change the diversity and aggressiveness of Fusarium species, which provides an important reference for effective management of this disease.